Եկեղեցական բնօրինակ փաստաթղթերի եւ հազուագիւտ գրքերի հաւաքածու Հայոց ազգագրութեան թանգարանում - Դաւիդովա, Գալեա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены подлинные документы, относящиеся к различным сферам церковной жизни. В документах, имеющих историко-культурное значение, обсуждаются вопросы церковного строительства и благотворительности, совершенствования системы образования и сохранения чистоты армянского языка. Большинство писем, хранящихся в коллекции, представляют собой поздравления по различным поводам и праздникам, которые заканчиваются богоугодными благословениями и пожеланиями. Заслуживает внимания одно из рукописных писем Католикоса всех армян Геворга VI, адресованное Его Высоко- преосвященству архиепископу Геворгу Арсланяну, в котором Его Святейшество поручает местоблюстителю Константинопольского патриархата подать жалобу президенту Турции на вмешательство во внутренние дела армянской церкви. Эти ценные, историко-культурные документы этнорелигиозной принадлежности раскрывают некоторые подробности истории армянской церкви. Армянский патриархат Константинополя всегда был сплочен и стремился сохранить трудную задачу оставаться армянином в чужой среде, сохранить армянский язык и армянскую культуру․ The article presents original documents related to various spheres of church life. In valuable documents of historical and cultural significance, issues of church building and charity, improvement of the education system and preservation of the purity of the Armenian language are discussed. Most of the letters stored in the collection are congratulations on various occasions and holidays, which end with God-pleasing blessings and wishes. Noteworthy is one of the handwritten letters of Catholicos of All Armenians Gevorg VI addressed to His Eminence Archbishop Gevorg Arslanyan, in which His Holiness instructs the Locum tenens of the Patriarchate of Constantinople to complain to the President of Turkey about interference in the internal affairs of the Armenian Church. These valuable historical and cultural documents of ethno-religious identity reveal some details of the history of the Armenian Church. The Armenian Patriarchate of Constantinople has always been united and has strived to preserve the difficult task of remaining an Armenian in a foreign environment, to preserve the Armenian language and culture in its original and pure form.
Keywords: Հաղորդումներ; Եկեղեցական գրականութիւն